2016
DOI: 10.2134/agronj15.0031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Legume Green Manures on Forage Produced in Continuous Wheat Systems

Abstract: Inorganic N fertilizers are important to continuous systems of winter wheat (Triticum aestivum L. em Thell.) in the U.S. southern Great Plains (SGP). Costs have increased in recent years and resulted in producers considering summer‐grown legumes as green N sources. This study (2008–2012) defined effects of lablab [Lablab purpureus (L.) Sweet ‘Rio Verde’] cover crops on subsequent forage production by wheat under conventional and no‐till management, compared to soybean [Glycine max (L.) Merr. ‘Laredo’], two ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…Additionally, the flux rates from cowpea treatments were significantly lower than from the 45-N and 90-N treatments. These results corroborate the previous findings in the region, as poor growth and yield responses of winter wheat to legume-based green N are reported frequently [3,4,25,27,28]. Lack of interaction effects between the tillage systems and N treatments indicated that cowpea-based green manure could not replace inorganic N fertilizers in either tillage system.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Additionally, the flux rates from cowpea treatments were significantly lower than from the 45-N and 90-N treatments. These results corroborate the previous findings in the region, as poor growth and yield responses of winter wheat to legume-based green N are reported frequently [3,4,25,27,28]. Lack of interaction effects between the tillage systems and N treatments indicated that cowpea-based green manure could not replace inorganic N fertilizers in either tillage system.…”
Section: Discussionsupporting
confidence: 90%
“…A possible reason for similar canopy CO 2 fluxes from the contrasting tillage systems might be related to the lower intensity tillage applied under CT, which was restricted to the upper 20 cm of soil, and residues were left on the soil surface. Previous studies in the SGP have documented similar yield responses of winter wheat to NT and CT systems [3,22,23], and were corroborated by similar levels of GPP for tillage systems in this study. The short distance between sites, and difference in soil properties and fertility, allowed a test of effects of nitrogen and tillage treatments across a broad set of landscapes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The past research mainly focused on the application of sewage sludge or green manuring in farmlands [31][32][33][34]. However, the application of sewage sludge combined with green manuring to amend mudflat salt-soils has received no attention.…”
Section: Introductionmentioning
confidence: 99%
“…Past research has defined the potential use of some grain legumes as forage sources during summer [1] [6] [7] [8] [9] [10]. However, many of the tested legumes have significant amounts of large-diameter, low digestibility stems in their aboveground biomass which limits their applicability for grazing [8].…”
Section: Introductionmentioning
confidence: 99%